Evaluation of Discretionary Authority on Immigration Supervision - Juan Carlo; Linus Abel Mahfud; Syahwa Salsabila (LEGAL BRIEF, 2022)
The purpose of this study is to find out the scope and executors who have discretionary authority in immigration control and find out what is the legal basis for consideration in using discretionary authority in enforcing immigration law? This writing uses a qualitative empirical normative approach through data collection and analysis techniques. The results of the discussion show that the limits of discretionary authority in immigration, including immigration officials (PPNS) as executors of discretion, the purpose and scope of discretion must be in accordance with applicable laws and regulations, and the exercise of discretion must be carried out in accordance with technical administrative procedures in the Administrative law Government. The implementation of discretionary powers is based on the guidelines of the principle of legality and general principles of good governance as well as the effectiveness and alternatives of immigration administration. It was concluded that immigration law enforcement officers (PPNS) exercise discretionary authority using the principle of legality as a benchmark for implementation and based on juridical and non-juridical considerations. It is recommended to be monitored and implemented strictly to avoid abuse of power.